(3GdOQ GdefThQ aj TQM UOQ OjhGf GdTPhQs - (3Ydj Hf eMeO Hf CjOeQ GdLdOcqj , YR GdOjf J (B742 (3g` s; (3GHf GQaY QGSg GdCfOdSj GdLjGfj, GHf GQaY QGSg GdCfOdSj GdLjGfj,J (B593 (3g` s ((3GdgQGI GdeMQhSI s)
(3ChdgG (B:s
(3hHYO , aEf ZQVi ai gPG GdcJGH Cf CTQM UOQ OjhGf TPhQ GdPgH ddYdeGA Ohf GdeJadSajf s
(3BNQgG (B:s
(3hcJH gPG GdcJGH ef fSNI cJHJ ef NW GdeUfa ecJhH YdjgG aQZ efgG jhe GdNejS JGSY YTQ QHjY GdChd ef SfI (B743 (3HGdbGgQI s
(3ai GdecJHI fSNI CNQi HQbe (B" 2015"s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs